Optoelectrofluidic Manipulation of Nanoparticles and Biomolecules. (15th November 2011) - Hwang, Hyundoo; Park, Je-Kyun
Abstract : This paper presents optoelectrofluidic technologies for manipulation of nanoparticles and biomolecules. Optoelectrofluidics provides an elegant scheme for the programmable manipulation of particles or fluids in microenvironments based on optically induced electrokinetics. Recent progress on the optoelectrofluidic manipulation of nanoobjects, which include nanospheres, nanowires, nanotubes, and biomolecules, is introduced. Some potential applications of the optoelectrofluidic nanoparticle manipulation, such as nanoparticles separation, nanostructures manufacturing, molecular physics, and clinical diagnostics, and their future directions are also discussed.